2020
DOI: 10.21203/rs.3.rs-43405/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clot Waveform of APTT Has Abnormal Patterns in Subjects with COVID-19

Abstract: In Coronavirus disease 2019 (COVID-19) subjects, recent evidence suggests the presence of unique coagulation abnormalities. In this study, we performed clot waveform analyses to investigate whether specific modulations are observed in COVID-19 subjects. We analyzed the second derivative of the absorbance in routine APTT tests performed using an ACL-TOP system. We observed high frequencies of abnormal patterns in APTT second-derivative curves that could be classified into an early shoulder type, a late shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…39 The clot waveform of APTT also suggested that COVID-19 patients might have distinctive abnormal coagulopathy. 40 High-level TIBIL is generally considered a marker of abnormal liver metabolism and hepatitis, 41 and there appears to be a significant relationship between HGB levels and COVID-19 disease severity. 42 These results suggested that enrolled COVID-19 patients may have liver damage, pathogen infection, and blood system disorder.…”
Section: Discussionmentioning
confidence: 99%
“…39 The clot waveform of APTT also suggested that COVID-19 patients might have distinctive abnormal coagulopathy. 40 High-level TIBIL is generally considered a marker of abnormal liver metabolism and hepatitis, 41 and there appears to be a significant relationship between HGB levels and COVID-19 disease severity. 42 These results suggested that enrolled COVID-19 patients may have liver damage, pathogen infection, and blood system disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a high SARS-CoV-2 viral load is associated with renal complications and the severity of COVID-19 (Caceres et al, 2021). Complications such as thrombosis and endothelitis are also frequently observed in COVID-19 subjects (Li et al, 2020, Shimura et al, 2021, Xiong et al, 2020; theoretically, such complications could lead to renal impairment. In addition, other mechanisms not specific to COVID-19 have also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The clot waveform of APTT also suggested that COVID-19 patients might have distinctive abnormal coagulopathy [27]. High-level total bilirubin is generally considered a marker of abnormal liver metabolism and hepatitis, and there appears to be a significant relationship between hemoglobin levels and COVID-19 disease severity [28].…”
Section: Discussionmentioning
confidence: 99%